Depolarization in c-cut tetragonal laser crystals. (7th December 2015) - Yumashev, K V; Loiko, P A
Abstract: Thermally induced birefringence and depolarization are described analytically for diode-pumped laser discs from [0 0 1]-cut tetragonal crystals. It is shown that the depolarization losses R can be minimized by an appropriate orientation of a polarizer with respect to the crystallographic axes. Calculations are performed for tetragonal scheelite-type molybdate laser crystals, Nd:PbMoO4, Nd:CaMoO4 and Nd:NaBi(MoO4 )2 . Nd:CaMoO4 provides the lowest depolarization losses, R < 15% with a very weak dependence on the absorbed pump power (for optimized light polarization, E || [1 1 0]).